EFFECT OF SOLANUM TRILOBATUM LINN ON MERCURY-INDUCED HEPATOTOXICITY IN SWISS ALBINO MICE - EKAMBARAM, MANIVANNAN (Journal of Drug Delivery and Therapeutics, 2012)
Solanum trilobatum Linn. has been evaluated for its hepatoprotective activity in Swiss albino mice using the mercury induced hepatotoxicity. The chloroform extract showed remarkable activity against mercury-induced hepatotoxicity as judged from biochemical parameters such as serum aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase (ALP) and levels of lipid peroxides (LPO) in liver. Animals treated with S. trilobatum extract before and after mercury intoxication showed a significant decrease in LPO level, AST and ALT activities and increase in ALP activity and glutathione (GSH) content. The extract treatment alone did not alter the biochemical parameters. The results suggest that oral administration of S. trilibatum provide protection against mercury induced toxicity in Swiss albino mice, but it was dose dependent, which was comparable to the control.